METODE AHP DALAM MENENTUKAN BAKAL CALON PRESIDEN RI 2024 - Syakbani, Tirta; Rohayani, Hetty; Handayani, Rahmi (Jurnal Informatika, Sistem Informasi dan Kehutanan (FORSINTA), 2023)
Approach is utilized to gather data through document analysis and in-depth interviews with various relevant stakeholders. The AHP method is used as a tool to rank and compare relevant assessment criteria to obtain a comprehensive overview of the This research aims to apply the Analytical Hierarchy Process (AHP) method in determining the prospective candidates for the 2024 Indonesian presidential election, namely Anies Baswedan, Ganjar Pranowo, Prabowo Subianto, and Ridwan Kamil. A qualitative strengths and weaknesses of each prospective candidate. This study is expected to provide an objective and transparent perspective in the context of selecting presidential candidates, as well as contribute to more accurate and informed decision-making